Molecular Characterization of Indonesian Indigenous Chickens based on Mitochondrial DNA Displacement (D)-loop Sequences - SRI SULANDARI; MOCH SYAMSUL ARIFIN ZEIN; TIKE SARTIKA (Bogor Agricultural University, Indonesia, 2008)
The Mitochondrial DNA (mtDNA) displacement (D)-loop sequences were used to study the genetic diversity and relationship of Indonesian indigenous chickens. A total of 483 individuals belonging to 15 population breeds and 43 individuals belonging to 6 populations of jungle fowl (2 populations of Gallus gallus and 4 populations of Gallus varius) were sampled. The hypervariable I (HVI) segment of the D-loop was PCR amplified and subsequently sequenced. The sequences of the first 397 nucleotides were used for analysis. Sixty nine haplotypes were identified from 54 polymorphic sites with polymorphism between nucleotides 167 and 397 contributing to 94.5% of the sequence variation. Phylogenetic analysis indicates that Indonesian indigenous chickens can be grouped into five distinct clades (clade I, II, IIIc, IIId, and IV) of the previously identified seven clades (clade I, II, IIIa, IIIb, IIIc, IIId, and IV) in Asian indigenous chickens. Fifty haplotypes belong to clade II, seven haplotypes are in clade IV, six are in clade IIId, three are in clade I and one haploype is in clade IIIc. There was no breed-specific clade. Analysis of Molecular Variance (AMOVA) based on partial D-loop sequences of Indonesian chicken indicates that 67.85% of the total sequence variation between haplotypes was present within the population and 32.15% between populations. One of the haplotypes (represented by PLC4) was shared by all populations, suggesting that these populations may share the same maternal ancestor. These results show a high mitochondrial D-loop diversity and indicate multiple maternal origins for Indonesian indigenous chickens. Key words: Indonesian indigenous chicken, mitochondrial DNA, D-loop, haplotype, phylogenetic analysis and clade